Zinc galvanized steel sheets crystal size influence in environments containing chlorides and sulfates - Ramírez-Jerez, Julieth Andrea; Valero-Alvarado, Mario; Peña-Ballesteros, Darío Yesid; Torres-Ramírez, Jhon Edisson (Universidad Pedagógica y Tecnológica de Colombia, 2015)
This paper studied the influence of the zinc crystal size in the electrochemical behavior of steel sheets hot-dip galvanized. The tests were performed in an electrochemical flat cell in solutions with different concentrations of NaCl and NaSO4. The rate, mechanism of corrosion and the resistive and diffusive characteristics of the sheets were tested by electrochemical techniques like electrochemical impedance spectroscopy (EIS), polarization resistance (Rp) and potentiodynamic polarization curves. The composition and distribution of the products of corrosion (FeO and some zinc compounds) and the surface damage caused by them, were determined using XRD and SEM-EDS. Results showed that the degradation of the oxide layer formed is affected by the presence of chlorides, which penetrate reaching the surface of the base metal, producing localized corrosion.